2004
DOI: 10.1021/bi049917r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofCisandTransFatty Acid Containing Phosphatidylcholines on Membrane Properties

Abstract: The ever-increasing amount of trans fatty acids in the human diet has been linked to a variety of afflictions, most notably coronary heart disease and arteriosclerosis. The mechanism of why the replacement of cis fatty acids with their trans counterparts can be detrimental to the health of an individual remains a mystery. Here, we compare the differences in membrane physical properties including molecular dynamics, lateral lipid packing, thermotropic phase behavior, "fluidity", lateral mobility, and permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 35 publications
5
120
1
Order By: Relevance
“…For the DPPC bilayer treated with the mixture of PBS and methanol (control), the sharp endothermic peak due to the phase transition from the gel phase to the liquid-crystalline phase was observed at 40.8°C. This temperature is lower than the phase transition temperature of pure DPPC reported by other researchers, 11,18) and the reduction in phase transition temperature occurred probably because of the effect of methanol in the treatment solution. Tran et al reported a similar effect induced by ethanol.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…For the DPPC bilayer treated with the mixture of PBS and methanol (control), the sharp endothermic peak due to the phase transition from the gel phase to the liquid-crystalline phase was observed at 40.8°C. This temperature is lower than the phase transition temperature of pure DPPC reported by other researchers, 11,18) and the reduction in phase transition temperature occurred probably because of the effect of methanol in the treatment solution. Tran et al reported a similar effect induced by ethanol.…”
Section: Resultscontrasting
confidence: 57%
“…There are many reports that perturbation of the lipid-packing order increases drug permeability. [11][12][13] In addition, recent studies have shown that altering membrane fluidity influences carrier-mediated transport, such as P-glycoprotein-mediated efflux. [14][15][16] Because DHA and EPA have multiple double bonds, they should change the lipid packing drastically.…”
mentioning
confidence: 99%
“…7,8 By their incorporation into the phospholipids in cell membranes, trans fatty acids may also alter the membrane function and decrease the membrane fluidity in a manner similar to saturated fat. 35 The prospective design of the preset study is a noteworthy strength; the occurrence of disease could not influence biomarker contents in erythrocytes and plasma. Moreover, we adjusted for major lifestyle and dietary risk factors for CHD and other classes of fatty acids in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of lipid monolayers at the air-water interface have made important contributions to our understanding of lipid-lipid interactions in lipid bilayers and are particularly useful to estimate the lateral area occupied by membrane molecules (21). However, it should be pointed out that cholesterol-lipid interactions in a monolayer are very different from those in a lipid bilayer.…”
Section: A Cholesterol-containing Monolayer At the Air-water Interfacmentioning
confidence: 99%